Qualidade da água de drenagem e salinidade do solo no Perímetro Irrigado Jacaré-Curituba no município de Poço Redondo – Sergipe - Santos, Jéssica Marcy Silva Melo (2021)
This study aimed to evaluate the quality of the drainage water of a saline-sodic soil under field conditions, and to analyze the salinity and sodicity of the soil in areas adjacent to a drainage channel in the Irrigated Perimeter Jacaré-Curituba, located in the municipality from Poço Redondo - Sergipe. The experimental design consisted of a completely randomized design, with nine water sampling points and three replications. The points being: beginning of the secondary drainage channel at the area (BSC), outlet of the secondary drainage channel of the experimental area (OSC), end drains of each plot (EDP1, EDP2, EDP3, EDP4, EDP5, EDP6) and water used in irrigation (WI) . Each experimental plot had an area of 200 m², so the experimental area occupied 1200 m². Six water sampling campaigns were carried out at nine points, one collecting the water used for irrigation, and eight at different points in the secondary drainage channel. Chemical analyzes of water quality parameters for irrigation were performed on the water samples. From the secondary drainage channel installed in the area of the experiment, an area of influence was delimited in the surroundings of the drainage channel according to topographic data of the place, obtained from the database of the Digital Atlas of Water Resources of the State of Sergipe, to collection and physical-chemical analysis of soil classification parameters for salinity and sodicity. Forty-six soil samples were collected, 23 at 0 – 15 cm in depth and 23 at 15 – 30 cm in depth. The results indicated by MANOVA showed that there was a main effect for the sampling points at campaign times, the interaction between the collection points also had a significant effect. Four different classifications for water were observed: C1S1; C3S1; C4S1; C4S2, 11.1%, 13%, 50% and 25.9%, respectively. For the soil, the results showed that 73.9% of the collection areas present soils classified as normal, for both depths, at a depth of 0 to 0.15 m, 17.40% of the soils were classified as saline-sodic and 8,70% as saline, and for a depth of 0.15 to 0.30 m the soils classified as saline and saline-sodic, represented 26.1%. It is concluded that the drainage water increased the concentration of Na in the drainage channel with potential for salinization of the soil, as for the soils of the adjacent area; the saline-sodic process shows the degree of salinity in the area.